Knowledge Sharing in the Process of Financial Administration in Hasanuddin University - Muh. Agung Paturungi; Otto R. Payangan; Hendragunawan S. Thayf (PINISI Discretion Review, 2023)
A challenge in knowledge sharing can also arise from a lack of understanding of the importance of knowledge and its advantages in enhancing organizational performance. Members of an organization may be less motivated to share knowledge if they are unaware of its significance and the benefits it can have on the company. To raise members of the organization's awareness of the importance of knowledge and its advantages, an effective communication strategy is required. What is the relationship between motivation (Mtv), information technology (Itc) and organizational climate (Ocl) on knowledge sharing (Ksh)? There are still few researchers who explore this question. The types of data that will be used in this study are qualitative data and quantitative data. The population and sample in this study were all employees of the Hasanuddin University Financial Administration Bureau. The analysis technique used is multiple linear regression analysis. The results showed that MTV, Itc, and Ocl had an effect on Ksh. Knowledge sharing activities within an organization can be influenced by a variety of factors, including motivation, information technology, and organizational climate. This understanding can be improved. High individual motivation can promote active involvement in knowledge sharing, and efficient information technology aids in knowledge exchange. On the other hand, an environment that is encouraging within an organization fosters a sense of comfort and motivation among its members to share knowledge. A challenge in knowledge sharing can also arise from a lack of understanding of the importance of knowledge and its advantages in enhancing organizational performance. Members of an organization may be less motivated to share knowledge if they are unaware of its significance and the benefits it can have on the company. To raise members of the organization's awareness of the importance of knowledge and its advantages, an effective communication strategy is required. What is the relationship between motivation (Mtv), information technology (Itc) and organizational climate (Ocl) on knowledge sharing (Ksh)? There are still few researchers who explore this question. The types of data that will be used in this study are qualitative data and quantitative data. The population and sample in this study were all employees of the Hasanuddin University Financial Administration Bureau. The analysis technique used is multiple linear regression analysis. The results showed that MTV, Itc, and Ocl had an effect on Ksh. Knowledge sharing activities within an organization can be influenced by a variety of factors, including motivation, information technology, and organizational climate. This understanding can be improved. High individual motivation can promote active involvement in knowledge sharing, and efficient information technology aids in knowledge exchange. On the other hand, an environment that is encouraging within an organization fosters a sense of comfort and motivation among its members to share knowledge.